Nuevas estrategias de mercado para el servicio de inspección de equipos y herramientas de la empresa SAIS S.A.S. (2019)
This is a project which seeks to provide a market alternative for the company SAIS S.A.S to not only dependent on the oil and gas industry as it currently does, but it comes to venture into new sectors looking for the necessary strategy to make it and turn resulting in further expansion market.